Education to live in the contemporary world: perceptions of students in catholic schools - Guimarães, Eder D’Artagnan Ferreira; Dabin, Pedro (Revista de Educação PUC-Campinas, 2021)
This article analyzes part of the data collected in a doctoral research linked to the National University of Rosario, Argentina. The research focused on the place of Catholic schools in the contemporary educational scenario based on the perception of the various actors in education (managers, educators, pastoralists, and students). It intended to problematize the perceptions of High School students about their experience of schooling. One hundred fifty-seven students from six Catholic schools in Belo Horizonte/MG presented their perceptions of school life through a written questionnaire and a drawing. The data were analyzed using Qualitative Epistemology and its concept of subjective meanings. Based on their experience in the Catholic school, the students: evaluate how plastered educational system prevents the development of integral educational processes focused on human development; report the traditionalism that runs through schooling today; demonstrate difficulty in identifying the school’s contribution to their formation and definition of life project; and attribute different meanings to the school education, according to their trajectory in the Catholic school.